2016
DOI: 10.1597/14-090r
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Reproducibility of Nonverbal Facial Expressions Using a 3D Motion Capture System

Abstract: There were no differences in magnitude and speed for maximal smile, cheek puff, and lip purse between the two captures for all participants. For individual expressions, maximal smile expression had the highest similarity value for individual landmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…These studies evaluated the repeatability of maximum motion state of expressions but did not consider that facial expression is a dynamic motion process. Another study evaluated expression reproducibility by comparing differences of the amplitude, speed, and similarity of the trajectory of the same facial landmark between repeated recordings (Ju et al, 2016). That research reflected the dynamic characteristics of facial expressions; however, the use of landmarks to analyze facial expressions still has its limitation: The characteristic landmarks mostly are distributed in the eyes, nose, and lips, while other positions such as the forehead and cheek could be overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies evaluated the repeatability of maximum motion state of expressions but did not consider that facial expression is a dynamic motion process. Another study evaluated expression reproducibility by comparing differences of the amplitude, speed, and similarity of the trajectory of the same facial landmark between repeated recordings (Ju et al, 2016). That research reflected the dynamic characteristics of facial expressions; however, the use of landmarks to analyze facial expressions still has its limitation: The characteristic landmarks mostly are distributed in the eyes, nose, and lips, while other positions such as the forehead and cheek could be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of 3-D static images ignored the dynamic characteristics of facial expressions. Ju et al (2016) selected special landmarks on the face and utilized a 3-D Motion Capture System to record the dynamic process of nonverbal facial expression. The similarity of the movement trajectories of facial landmarks represented the repeatability of facial expressions.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest a stark difference in the reproducibility of facial expressions between healthy individuals and those suffer from unilateral facial paralysis. It has been shown that maximum smile is one of the reproducible facial expressions in those who do not suffer from facial paralysis (29) .…”
Section: Discussionmentioning
confidence: 99%
“…Soft-tissue facial movements can be noninvasively captured and quantified by 3D motion analyzers 5,14,22,23,[25][26][27][28][29] . Among others, optoelectronic motion systems offer a valuable support for extracting objective measurements by positioning markers in standardized anatomical points 23,[27][28][29][30][31] . 4 The aim of this longitudinal study is to analyze the pre-surgery versus post-surgery differences in verbal and nonverbal soft-tissue facial movements in a group of patients with dentoskeletal Class III, candidates to bimaxillary orthognathic surgery.…”
Section: Introductionmentioning
confidence: 99%